New Paleomagnetic Results From Middle Jurassic Limestones of the Qiangtang Terrane, Tibet: Constraints on the Evolution of the Bangong‐Nujiang Ocean. Issue 1 (21st January 2019) - Cao, Yong; Sun, Zhiming; Li, Haibing; Pei, Junling; Liu, Dongliang; Zhang, Lei; Ye, Xiaozhou; Zheng, Yong; He, Xiangli; Ge, Chenglong; Jiang, Wan
Abstract: To constrain the relationship between the Qiangtang and Lhasa terranes and the evolution of the Bangong‐Nujiang Ocean (BNO), we carried out a paleomagnetic investigation of the Middle Jurassic limestone from the Shuanghu region in the southern Qiangtang terrane. Stepwise thermal demagnetization succeeded in isolating high‐temperature characteristic directions by either principal component or great circle fitting analyses. The site‐mean direction of the 13 sampling sites was Dg = 334.7°, Ig = 51.2°, kg = 27.9, α 95 = 8.0° (in geographic coordinates) and Ds = 245.2°, Is = 54.1°, ks = 113.9, α 95 = 3.9° (in stratigraphic coordinates). The paleomagnetic data passed both fold and reversal tests. Both rock magnetic and petrographic investigations suggest a primary magnetization. The paleomagnetic results imply that the paleolatitude of the Qiangtang terrane was 34.6 ± 4.6°N (reference site: 32.7°N, 89.4°E) in the Middle Jurassic. Combined with previous reliable paleomagnetic results, it is suggested that the Qiangtang terrane was situated at a stable paleolatitudinal position and did not undergo obvious N‐S displacement between the Late Triassic and the Middle Jurassic. Comparison with the paleomagnetic results available for the Lhasa terrane implies that the width of the BNO was 2, 600 ± 710 km (23.4° ± 6.4°) during the Middle Jurassic. The BNO expanded from the Early to Middle Triassic, reached its maximum width in the Late Triassic, and then shrank until it closed by the Cretaceous. Key Points: The Qiangtang terrane was situated at 34.6 ± 4.6°N in the Middle Jurassic (reference point: 32.7°N, 89.4°E) The Qiangtang terrane did not undergo obvious latitudinal displacement between the Late Triassic and the Middle Jurassic The Bangong‐Nujiang Ocean reached its maximum width in the Late Triassic and then shrank until it closed by the Cretaceous